Complex issues made clear - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Food security in Africa: a development challenge Dossier Agripromo, INADES-Formation CTA - Solagral, 2001. 102 pp. ISSN 1018 8568 CTA number 1064, 20 credit points.